2016
DOI: 10.1021/acs.joc.5b02583
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Diels–Alder Reactivity of Substituted [4]Dendralenes

Abstract: The first synthesis of all five possible monomethylated [4]dendralenes has been achieved via two distinct synthetic strategies. The Diels-Alder chemistry of these new dendralenes (as multidienes) with an electron poor dienophile, N-methylmaleimide (NMM), has been studied. Thus, simply upon mixing the dendralene and an excess of dienophile at ambient temperature in a common solvent, sequences of cycloadditions result in the rapid generation of complex multicyclic products. Distinct product distributions are obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…interesting strategy involves the use of the DA reaction in tandem protocols 20,21 for rapid and 13 efficient access to diverse libraries of complex products 22 and target molecules. 23,24 14 In the framework of our studies on aldol condensation reactions, we have reported the 15 synthesis of a series of styrylcyclohex-2-enone dienes (e.g.…”
mentioning
confidence: 99%
“…interesting strategy involves the use of the DA reaction in tandem protocols 20,21 for rapid and 13 efficient access to diverse libraries of complex products 22 and target molecules. 23,24 14 In the framework of our studies on aldol condensation reactions, we have reported the 15 synthesis of a series of styrylcyclohex-2-enone dienes (e.g.…”
mentioning
confidence: 99%
“…[1] No longer simply molecules of curiosity, in large measure due to the efforts of pioneers such as Hopf, and more recently Sherburn, dendralenes of both the cyclic and acyclic varieties have become useful intermediates in targeted syntheses (Figure 1, bottom). [2,3] One of many attractive features is their ready participation in cycloaddition reactions, in particular the diene-transmissive-Diels-Alder (DTDA) reaction. In this regard, they are well configured to maximize "step economy" en route to both natural and unnatural materials that contain polycyclic arrays.…”
mentioning
confidence: 99%
“…This multi-catalytic system applied to the synthesis of functionalized dendralenes shows broad substrate compatibility, as well as functional group tolerance. Furthermore, these mild conditions compare very favorably with existing methods, [1,2,4,6] in terms of simplicity, amounts of reagents involved, and environmental concerns (such as organic waste in the form of solvents, and energy invested in the form of low temperatures).…”
mentioning
confidence: 99%
“…[1] No longer simply molecules of curiosity,i nl arge measure due to the efforts of pioneers such as Hopf,a nd more recently Sherburn, dendralenes of both the cyclic and acyclicv arieties have become useful intermediates in targeted syntheses (Figure 1, bottom). [2,3] One of many attractive features is their ready participation in cycloaddition reactions,i np articular the diene-transmissive-Diels-Alder (DTDA) reaction. In this regard, they are well configured to maximize "step economy" en route to both natural and unnatural materials that contain polycyclic arrays.N otwithstanding the remarkable advances made in preparing higher homologs that now have reached [12]dendralene, [4] recent papers from the Sherburn group highlight the need for additional inroads to both the parent and especially substituted systems,a sw ell as new chemistry that extends the repertoire of reactions of dendralenes beyond [4+ +2] cycloadditions.I ndeed, in ar ecent Account, [5] Sherburn concludes:" Regarding our deployment of the dendralenes and related unsaturated hydrocarbons in the rapid generation of structural complexity,a gain, we have deployed only knownreactions (and in the main, just one:the venerable Diels-Alder reaction).…”
mentioning
confidence: 99%
“…Thus,a crylates,a crylamides,s tyrenes,a nd other alkenes readily participated under similar micellar conditions,p roviding the corre-sponding Heck products in good isolated yields.N oteworthy is the realization of substituted enoates at their b-positions (e.g., 3)w ithout observable isomerization. Furthermore,t hese mild conditions compare very favorably with existing methods, [1,2,4,6] in terms of simplicity,amounts of reagents involved, and environmental concerns (such as organic waste in the form of solvents,a nd energy invested in the form of low temperatures). Borylation was initially [6h] Of note is that homocoupling does not occur under copper catalysis even after extended reaction times (i.e., from 2to48h).…”
mentioning
confidence: 99%